Terminology of the Thalamus and its Representation in a Part-Whole Relation - Axer, H.; Niemann, K. (Methods of Information in Medicine, 1994)
In stereotaxic neurosurgery, a variety of operative procedures focus on thalamic targets. The nomenclature of thalamic nuclei and sub-nuclei, however, has not yet been settled. In clinical and laboratory environments several terminologies coexist. This is an obstacle to both communication and a better understanding of recent electrophysiological findings. In the late 1980s, the application of new histochemical and immunohisto-chemical methods led to a deeper insight into existing correlations between the nomenclatures. As a uniform terminology of the thalamus is still lacking, we created a knowledge-based system (thalamus) which gives a comprehensible survey about the most important terminologies. The different nomenclatures are related to each other by organizing them in a component-integral relation. This part-whole relation contains both the knowledge on the subdivisions of the thalamus as well as the knowledge on the correlations between the various nomenclatures.
Keywords: Terminology; Thalamus; Merologisms; Databases; Stereotaxy